Análise fitoquímica e avaliação das atividades antioxidante e antimicrobiana de Maytenus ilicifolia (Mart. ex Reissek) - Oliveira, Raul Moreira (2016)
Despite the World Health Organization recognize the relevance of medicinal plants use by population to treat some health conditions, in some plant species, leaves are prepared from different forms without any criteria and previous efficacy and safety evaluation of each infusions preparation. This is the case of Maytenus ilicifolia Mart. ex Reissek (Celastraceae), popularly known as Espinheira-Santa. Popularly, this specie is used as infusion prepared from fresh or dried leaves. Therefore, the aim of this study was to evaluate the existence of potential differences of M. ilicifolia fresh and dried leaves extracts on bioactive molecules composition, antioxidant capacity and antimicrobial activity against 12 bacteria strains. Moreover, the effect of M. ilicifolia extracts on reactive oxidative species (ROS) modulation of bacteria were also investigated. Hydroalcoholic extracts using fresh and dried M. ilicifolia leaves were obtained and the quantification of eight bioactive molecules was performed by HPLC-DAD protocols. Antioxidant capacity and antibacterial effect were also evaluated. The M. ilicifolia extract produced from dried leaves presented higher concentration of bioactive compounds (mainly quercetin and caffeic acid), as well as a more efficient antibacterial activity despite the antioxidant capacity to be higher in fresh leaves extract. Both extracts at different concentrations decreased ROS levels. As concomitant antibacterial and antioxidant activities were observed in M. ilicifolia extracts, the results suggest that decreasing of ROS levels could cause cytotoxicity by reductive stress or to act as inhibitory signaling of bacteria proliferation. Complementary studies need to be perform to corroborate this hypothesis. The results presented here could be relevant, since show important impact of leaves preparation on extraction of some chemical compounds and the biological activities of M. ilicifolia.